The ZZZ adult academic reading model / Faizah Abd Majid, Zalizan M Jelas and Norzaini Azman - Abd Majid, Faizah; M Jelas, Zalizan; Azman, Norzaini (Pusat Penerbitan Universiti (UPENA), 2005)
Research on academic reading has resulted in lists of strategies employed by the proficient and the less proficient readers. Nonetheless, not much research has attempted to investigate the academic reading strategies of adult learners by considering the potential influence of their common characteristics: experience, selfconcept and time perspective. This study examined in depth the academic reading strategies of four adult learners by considering the influence of these common characteristics. After providing the synopsis of the reading models, examples of academic reading strategies and theories on adult learners, this article describes the study's methodology, findings, and implications. The findings indicate that the proficient adult readers in this study were able to manipulate their characteristics to the advantage of their academic reading. Based on the findings, the ZZZ Adult Academic Reading Model was designed. It is hoped that this model will guide adult educators as well as adult learners in academic reading classes.